(untitled) (National Administration Journal, 2021)
The present paper analyzed the economic, social, and environmental dimensions of cooperatives sustainability and examined the sustainability oriented competitive strategies adopted by sample cooperatives. Field survey method will be followed. Multi-stage sampling method was adopted to select study area, cooperatives and respondents. Six cooperatives and by adopting PPS 100 members were selected. The sustainability score card approach advocated by Measuring Cooperative Difference Research Network (MDCRN), Canada and Morris Inequality Index were used. The result shows that the agricultural cooperatives do have better position with economic sustainability, to some extent social sustainability, but they do not have favourable situation in environmental sustainability so that the cooperatives are located at moderate and low level of sustainability condition. With regard to comprehensive cooperative sustainability the same result is seen among sampled cooperatives. Sustainability level and ranking are in consonance with the strategies they adopted and right strategy at right time effectively is advocated.